Magnetostratigraphic dating of the danangou and dongyaozitou mammalian faunas in the Nihewan Basin, North China. (1st April 2021) - Liu, Ping; Qin, Huafeng; Li, Shihu; Yuan, Baoyin
Abstract: The fluvio-lacustrine sequences in the Nihewan Basin of North China are rich sources of mammalian faunas and Paleolithic sites, thus providing unique insights into our understanding of land mammal biochronology and early human settlements in East Asia. Among the Nihewan Fauna ( sensu lato ), the Danangou (DNG) and Dongyaozitou (DZ) faunas are two of the important Pleistocene and Pliocene mammalian faunas in the Nihewan Basin. Except for a biostratigraphy, precise age control on the DNG and DZ faunas remains unavailable. Here we report high-resolution magnetostratigraphy results that stringently constrain their ages. The results show that the DNG sequence recorded the Brunhes normal chron, the Matuyama reverse chron and the late Gauss normal chron, yielding the fossil-rich layers of DNG fauna with an age of ca. 1.95 Ma to 1.78 Ma during the Olduvai normal subchron. The DZ sequence was located at the late Gauss normal chron, yielding an age of ca. 3.04–2.58 Ma before the termination of the Kaena reverse subchron. Highlights: We report a new magnetostratigraphy on the Danangou and Dongyaozitou faunas in the Nihewan Basin, North China. Magnetostratigraphic results give the fossil-rich layers of DNG fauna with an age of 1.95–1.78 Ma. The results show DZ fauna is about 3.04–2.58 Ma extending to late Pliocene. The chronology of the well-known Nihewan faunas has been significantly improved.